HISTORY OF METHYL BROMIDE FUMIGANT, METHODS OF USE, TECHNICAL SAFETY REQUIREMENTS FOR USE - Murodov B. E.; Shaymanov M. Sh.; Avazov S. S.; Qodirov N. Q.; Sulaymonov I. N. (Web of Journals Publishing, 2025)
This article provides information about the history of methyl bromide, its uses, contraindications to the use of the fumigant, and the effects it has on the human body when used improperly.